Methods for behavioral testing of spinal cord injured rats - Sedý, Jirí; Urdzíková, Lucia; Jendelová, Pavla; Syková, Eva (Neuroscience and biobehavioral reviews, 2008)
Behavioral outcome in rats with spinal cord injury (SCI) is the most important factor for evaluating the extent of injury and treatment efficacy. For this purpose, a number of behavioral testing methods can be used. In this review, 35 individual locomotor, motor, sensory, sensory-motor, autonomic or electrophysiological behavioral tests, their weaknesses and strengths, testing conditions, the need for habituation, pre-training and/or food deprivation, methods for increasing the animals' skills, systematic testing protocols and methods for selecting the proper behavioral tests for particular injury models are discussed on the basis of a retrospective analysis of scientific studies published from 1995 to 2007. This review is primarily targeted towards researchers outside the field or to researchers new to the field of SCI.
Keywords: Motor Skills; motorické dovednosti; obnova funkce; Disease Models, Animal; behaviorální výzkum; Rats; modely nemocí na zvířatech; poranění míchy; zvířata; Recovery of Function; regenerace nervu; Behavioral Research; Spinal Cord Injuries; Nerve Regeneration; krysa rodu Rattus; Animals